Effect of Plant Population and Weed Management Practices on Weed Dynamic and Crop Performance in Transplanted Basmati Rice (Oryza sativa L.) - Kishore, Roop; Singh, Raghuvir; Dwivedi, Ashish; Bankoti, Priyanka; Prakash, Jai; Thaneshwar; Shahi, U. P. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was carried out during summer seasons of 2009 and 2010 at CRC of SVPUA and T, Meerut India. Treatments comprising 4 planting geometries as main plot and 5 weed management in a split plot design with 3 replications by using F test. Experimental result revealed that plant population of 50 plants m-2 proved significantly superior over 20 plants m-2 in respect of weed density, weed dry weight at 90 DAT. Though, growth parameters viz., plant height, dry matter accumulation and No. of tillers m-2 at 90 DAT, grains weight panicle-1, grain yield (29.00 and 31.00 q ha-1), protein content, protein yield and N, P and K content in grain and straw were recorded with 50 plants m-2 followed by 40 plants m-2 during 2009 and 2010, respectively. As far as weed management practices was concerned, both chemical and mechanical methods of weed control were found significantly superior over weedy check in respect of lowest weed density and dry weight highest at 90 DAT although, significantly maximum growth parameters at 90 DAT, grains weight panicle-1 grain yield of 30.40 and 32.60 q ha-1, protein content, protein yield and N, P and K content in grain and straw were recorded with two hand weedings which was on par with Butachlor @ 1.0 kg a.i. ha-1 fb one hand weeding over rest of the weed management practices.